An ideal relationship between central and regional authorities in Indonesia: The 1945 constitution perspective - Tiopan, Demson; Kurniawan, Shelly; Stevie, Stevie (Technium Social Sciences Journal, 2023)
Indonesian central and regional government relationship often changes along with domestic political development and people’s needs. Law no. 1/1945 contained the concept of Indonesia’s autonomy with people’s sovereignty, and Law no. 22 of 1948 contained the concept of ‘the broadest economy.’ During the 1950 Provisional Constitution era, Law no. 1/1957 and Law no. 6/159 contained the concept of real and broadest autonomy. During the 1945 Constitution in New Order Era, presidential decree No. 6 of 1959 stipulated the real and broadest autonomy, in addition to Law no. 18/ 1965 with a similar concept and deconcentration principle, Law no. 5 /1974 on real and responsible autonomy, stipulating that decentralization is equally important to deconcentration, Law no. No. 22 of 1999 stipulated the real and broadest autonomy, in addition to Law no. 32/2004 on the amendment of real autonomy. Law no. 23 of 2014 tends to adhere to the deconcentration principle. This normative legal study employed secondary data sources, including the 1945 Constitution, Law no. 22/1999 on local government, Law no. 32/2004 on local government, Law no. 23/2014 on local government, Law no. 9/2015 on the second amendment of Law no. 23/2014 on local government, and relevant books, articles, and papers.